Collective Memory and the Definition of Place: A Monument for the Winnipeg General Strike of 1919 - Hyland, Gillian Crawford (University of Manitoba, 1995)
ln acknowledging and incorporating significant episodes of the past into the present landscape, monuments can provide the inhabitants of a place with an interactive heritage: a heritage based on the fusion of past and present, deepening a sense of place by providing the means to possess a common identity, that is to belong to a fellowship of place. The intent of this practicum was the development of a contextually based monument which relies on an integration of elements and contextual relationships to convey its meaning. With this goal in mind, the evolution of the monument was studied in order to gain a better understanding of it as a theoretical concept and valid functional element. The intent of this study was the development of programmatic guidelines for a contextually based monument. The Winnipeg General Strike of 1919 provided the perfect subject for the design of a commemorative monument which would be based on an application of the developed program. Site selection for this specific commemorative monument was based on the applicability to historical criteria and thematic issue derived from a study of the Winnípeg General Strike. ln addressing and defining each of the requirements, the design has achieved its purpose in illustrating the practical application of a theoretical concept, the contextual monument.